Risk analysis for mega commercial projects - Ibrahim, Hesham (AUC Knowledge Fountain, 2015)
Mega shopping mall projects have seen dramatic growth and great development in recent years in Egypt. In addition, many new Mega shopping mall projects are under construction and expecting to start working in the few coming years. In the absence of researches studying the Egyptian Mega shopping mall projects, this study tries to highlight the most critical risks that face the Mega shopping mall projects in Egypt and the associated most effective response methods currently employed in Egypt. Through a comprehensive literature search and via a questionnaire survey, this research identifies the most critical risks that face the Mega shopping mall projects in Egypt and the associated most effective response methods currently employed in Egypt. The scope covers the analysis from different perspectives by including Owners/Developers, Designers, Consultants, Project Managers, and Contractors that have previous experience in large scale projects such as shopping mall projects. In this study, 30 construction project risks are classified into six main categories according to their type and 150 risk mitigation/elimination measures are introduced to overcome the impact of risks under each of these risk categories. The results reveal that the main risk category that faces the Mega shopping mall projects in Egypt is the one including the financial risk factors. The most critical risk factor that faces the Mega shopping mall projects in Egypt is the financial ability of the client. This was similar to findings from the Egyptian construction industry by Orabi (2003), the Sudanese construction industry by Alwan (2006) and in Chinese construction industry by Tang et al. (2007). Other top critical comparable risks were concerned with changing needs, approvals and permits, and resources unavailability are identified in various countries and are top ranked terms of their impact on the Mega shopping mall projects. Based on the examining study to clarify how a sample of contracts responded to the most critical risks in these kinds of specialized projects, it was concluded that using contractual measures was the key response method that was perceived by all different participants as the most effective method to eliminate/mitigate the effect of most of the risks considered in this research.